Ledkov’s Novella White Hawk: A Nenets Epic Reconstruction - Kudrjavtseva, Tatjana (Journal of Northern Studies, 2008)
This article presents a reading of the “epic novella” White Hawk by the Nenets writer Vasilij Ledkov, which was published in 1982, in the last decade of the Soviet Union. White Hawk is an epic reconstruction from a Nenets point of view of the historical events that are otherwise recorded only by the Russian colonisers. These events are known as “the century of wars” between the Nenets and the Russians prior to the subjugation of the Nenets to Russian rule. In other Soviet sources on the Nenets this century of wars has been passed over in silence. In the late Soviet period, in 1982, Ledkov attempted to loosen the constraints of what was permissible, while at the same time he sought to protect the text from condemnation by allowing for a number of divergent readings. He may have done this not least in order to avoid the accusations of nationalism to which he had previously been subjected. It is my contention that the text must have appealed to the particular type of Soviet reader who was aware of the practice of double coding as a way of loosening ideological constraints. Such a reader would be willing to disregard the elements of the text that gave it ideological legitimacy and would have a keen eye for innovative – or what were previously “nonpermissible” – elements. Not a few Soviet authors are known to have participated in the development of an increasingly more Aesopian language, and it would be a mistake to view writers from the Northern peoples as less capable in this respect.